Quizizz Paper Media in Improving Understading of Tayamum - Hanny Triyuniarti; Nurul Fadila; Imam Tabroni; Morse Kathryn; Woolnough Cale (Yayasan Adra Karima Hubbi, 2023)
Background. The rapid development of science and technology today can be felt and affects human life (Kinuthia & Marshall, 2013). In education, technology has a real positive impact on learning. Students can access more and faster information from various sources Purpose. With the utilization of technology, the teaching and learning process becomes more enjoyable and innovative. Method. According to Law number 20 of 2003 article 40 paragraph 2 states that educators and teaching staff are obliged to create a meaningful, fun, creative, dynamic and dialogical educational atmosphere. Creating fun learning can be done by using media in learning (Kusnardi C, 2020). Results. , Judging from the facts in the field, where students have many difficulties in learning fiqh learning, especially about tayamum, starting from the conditions of tayamum, the pillars of tayamum and the implementation of tayamum (Abidin, 2020). Conclusion. This can be evidenced by the lack of focus of students on learning and the lack of students on the material to be taught. In addition, students will be bored with monotonous learning. It is necessary to update the learning media in the form of game-based media and technology used by teachers to be able to attract students optimally